Land Use Explains the Distribution of Threatened New World Amphibians Better than Climate - Brum, Fernanda Thiesen; Gonçalves, Larissa Oliveira; Cappelatti, Laura; Carlucci, Marcos Bergmann; Debastiani, Vanderlei Júlio; Salengue, Elisa Viana; dos Santos Seger, Guilherme Dubal; Both, Camila; Bernardo-Silva, Jorge Sebastião; Loyola, Rafael Dias; da Silva Duarte, Leandro (PloS one, 2013)
We evaluated the direct and indirect influence of climate, land use, phylogenetic structure, species richness and endemism on the distribution of New World threatened amphibians. We used the WWF's New World ecoregions, the WWFs amphibian distributional data and the IUCN Red List Categories to obtain the number of threatened species per ecoregion. We analyzed three different scenarios urgent, moderate, and the most inclusive scenario. Using path analysis we evaluated the direct and indirect effects of climate, type of land use, phylogenetic structure, richness and endemism on the number of threatened amphibians in New World ecoregions. In all scenarios we found strong support for direct influences of endemism, the cover of villages and species richness on the number of threatened species in each ecoregion. The proportion of wild area had indirect effects in the moderate and the most inclusive scenario. Phylogenetic composition was important in determining the species richness and endemism in each ecoregion. Climate variables had complex and indirect effects on the number of threatened species. Land use has a more direct influence than climate in determining the distribution of New World threatened amphibians. Independently of the scenario analyzed, the main variables influencing the distribution of threatened amphibians were consistent, with endemism having the largest magnitude path coefficient. The importance of phylogenetic composition could indicate that some clades may be more threatened than others, and their presence increases the number of threatened species. Our results highlight the importance of man-made land transformation, which is a local variable, as a critical factor underlying the distribution of threatened amphibians at a biogeographic scale.